(3fRgI GdCSeGY hGdCHUGQs - (3GdLQehRjs
(3ChdgG (B:s
(3GdMeO ddg Gdbjhe Ydi Ndbg hHYO aEfg MOGfi GdYJQI GdfHhjI cJHJ LedkG HSjQI eY hSjY SjQI ehdGfG hEeGefG GdefUhQ HGddg CejQ GdeDefjf GdbGSe Hf eMeO s
(3BNQgG (B:s
(3Je ceG hLO ef SjQI Gdehdi CejQ GdeDefjf GdeJhcd Ydi dGdg ESeGYjd Hf GdbGSe Hf eMeO Hf QSh Gddg Udi Gddg Ydjge CLeYjf s
(3ai SjQI GdeJhcd Ydi Gddg ESeGYjd Hf GdbGSe Hf eMeO Hf QShds
(3hHOC HSjQI hGdOg GdbGFe Hf eMeOs
(3hBNQ eG ajg ef GdMhGOK ai SfI (B1059 (3g`s
(3cJHJ GdYfGhjjf HGdNVQI hGdMeQI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs